Shaming by international organizations: Mapping condemnatory speech acts across 27 international organizations, 1980–2015. (September 2019) - Squatrito, Theresa; Lundgren, Magnus; Sommerer, Thomas
In the face of escalating conflicts or atrocities, international organizations (IOs), alongside non-governmental organizations (NGOs), often vocalize public condemnation. Researchers have examined NGO shaming, but no extant literature has comparatively explored if, how and why IOs shame. This article fills this gap. We conceptualize IO shaming as condemnatory speech acts and distinguish between the agent, targets and actions of shaming. We theorize how compliance and socialization are motives that lead IOs to shame. Empirically, we use new data on more than 3000 instances of IO shaming, covering 27 organizations between 1980 and 2015 to examine empirical patterns across the three dimensions of agents, targets and actions. We find that the majority of IOs do employ shaming but to varying degrees. Global, general-purpose IOs shame the most and regional, task-specific IOs the least. IOs mainly shame states, but there is a rise in the targeting of non-state and unnamed actors. While many condemned acts relate to human rights and security issues, IOs shame actions across the policy spectrum. These findings indicate that IO shaming is driven by compliance and socialization motives and that it is a wider phenomenon than previously recognized, suggesting possible avenues for further inquiry.